Medial collateral ligament release during knee arthroscopy - da Silva Campos, Vicente Carlos (2021)
Publisher Copyright: © 2021. The author(s) This article is distributed under the terms of the Creative Commons Attribution-Non Commercial 4.0 International (CC BY-NC 4.0) licence (https://creativecommons.org/licenses/by-nc/4.0/) which permits non-commercial use, reproduction and distribution of the work without further permission provided the original work is attributed.